Eucalyptus urophylla S.T. Blake: ecology and silviculture in Vietnam - Sein, C.C.; Mitlöhner, Ralph (Center for International Forestry Research, 2011)
This manual summarises information on the ecology and silviculture of the species Eucalyptus urophylla S.T. Blake, with an emphasis on Vietnam. It also encompasses growth and yield data from published sources, as well as collected from sites under smallholder industrial plantations in Binh Dinh and Phu Tho provinces, Vietnam. This manual is 1 of 5 that guide smallholder tree planting of five selected tree species in Vietnam. The other four species are: Acacia hybrid, Acacia mangium Willd, Cinnamomum parthenoxylon (Jack) Meisn and Erythrophloeum fordii Oliver.